A Study Paper on Communication Network and overview of Packet Switching Technology - Panwar, Sandeep; Garg, Amit; Kumar, Naresh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper,we highlight some of the principal events that led up to the revolution in communications among information processing systems. We devote most of this presentation to a brief summary of the communication networks experience, emphasizing the description, functions, analysis, design and performance measurement of packet-switching networks. We also discuss some recent advances in radio packet switching for long-haul